Chapter 8 Localism and political systems in the twenty-first century - Harmes, Rick (Taylor & Francis, 2021)
This final chapter focuses on the design of political institutions and systems. Not only is design thinking a key element of an engaged political analysis (Stoker, 2013), but it is also particularly relevant at the present time, as countries struggle with the Covid-19 pandemic which has engulfed the world during 2020.